Streetscape planning methodology and development scenarios. Terbatas street example in Riga - Ņitavska, Natalija; Skujāne, Daiga; Markova, Madara (Landscape Architecture and Art, 2024)
The proportion of intensive building and pavement of the urban environment reduces the level of comfort of the population, thus, the streets are nowadays considered to be the essential public outdoor space, where it is necessary to increase the comfort and well-being of the population by reducing the transport load. Historic urban centres are often characterised by relatively narrow streets, without planting and with the intensive traffic, consequently, solutions need to be found to humanise these outdoor spaces. The publication provides the authors’ experience in working with the planning of the preliminary research of Riga Terbatas Street and choosing a scenario method that is important for decision-making – because opportunities and options have to be evaluated according to the needs of the city residents and further development of the urban environment. The limited outdoor space of the street is a major challenge where it is necessary to realize both safety, environmental accessibility, ecological, aesthetic and cultural and historical ambitions and tasks. In the times of urban dynamism and variability, there is an important discussion with the public and non-governmental organisations: for this purpose, the scenario method allows some action plans to be evaluated and a decision to be taken for further design. The publication also contains a number of street planning principles to be used in the landscape architecture as validation for concepts and analytical summary of good practice examples. In the planning example, Terbatas Street in Riga has been chosen, which is one of the typical streets of historic centre of Riga, but with its charm and history. The research was carried out within the framework of the project for development of the initial technical documentation of the construction intention “The development of the public outdoor space and promotion of accessibility of Riga Centre and the neighbourhood of Brasa”.